Basic science of dermoscopy - Balachandra S Ankad; S V Smitha; Varsha R Koti (Wolters Kluwer Medknow Publications, 2020)
Introduction: Dermoscopy is a non-invasive tool which demonstrates characteristic patterns in many dermatoses. To understand dermoscopy, basic elements, vascular structures and pigment netwrok should be dealt with. One needs to understand the concept of basic physics of dermoscopy and cross polarization. Non-polarized and polarized lights show particular patterns in prominence. Hence both are complementary to each other. It is recommended to use both lights in clinical practice. Essentially, dermoscopic features should be analyzed and interpreted in terms of pattern of dermoscopic changes, predominant color and any specific clues present in the lesion. This is basic approach to a given lesion to arrive at accurate diagnosis dermoscopically. Aim: To understand the basic principles of dermoscopy and the types of dermoscopy. Summary: Dermoscopy is a rapid method that involves the use of a hand-held device with a built-in illumination and magnification systems. It is an in-vivo technique to observe the surface and subsurface structures in the skin layers. In the past, it was employed exclusively to diagnose and rule out melanoma in a given pigmented lesion. Its confirmed utility in inflammatory and infective dermatoses has enhanced its popularity as dermatologist's stethoscope.